Are indigenisation measures compensable? a case study of measures taken under the indigenisation and economic empowerment laws of Zimbabwe - Soyeju, Olufemi Olugbemiga (University of Pretoria, 2015)
Dissertation (LLM)--University of Pretoria, 2014.